Integration or minimalism: twenty-one new species of ghost spiders (Anyphaenidae: Anyphaena) from Mexico - Rivera-Quiroz, Andrés; Álvarez-Padilla, Fernando (European Journal of Taxonomy, 2023)
The rhythm of biodiversity loss vastly surpasses the number of new species described per year, with several taxa going extinct without us even knowing about their existence. After more than 250 years of traditional taxonomy, it is clear that the rate of biodiversity description and discovery needs to be improved. Molecular data has greatly increased the speed of species discovery and accuracy of taxonomic delimitation. Phenotypic documentation, although relatively slower, is still crucial to identify species and communicate taxonomic discoveries to a broader audience. Here, we integrate these data sources to describe a relatively large number of new species of the spider genus Anyphaena and look into its internal phylogenetic relationships. Our findings support the existence of several species groups within Anyphaena (as currently defined), but failed to recover the monophyly of this genus, suggesting a more comprehensive revision of its species groups and closely related anyphaenid genera is necessary. The 21 new species described here are: Anyphaena adnani sp. nov., A. bifurcata sp. nov., A. dulceae sp. nov., A. epicardia sp. nov., A. fernandae sp. nov., A. franciscoi sp. nov., A. ibarrai sp. nov., A. jimenezi sp. nov., A. megamedia sp. nov., A. miniducta sp. nov., A. natachae sp. nov., A. noctua sp. nov., A. porta sp. nov., A. quadrata sp. nov., A. rebecae sp. nov., A. salgueiroi sp. nov., A. sofiae sp. nov., A. stigma sp. nov., A. tonoi sp. nov., A. triangularis sp. nov. and A. urieli sp. nov.